PERAN KEPALA SEKOLAH SEBAGAI MOTIVATOR DALAM MENINGKATKAN PROFESIONALISME KINERJA GURU DI SDN 2 KALIREJO PESAWARAN - Nikmah, Mulyatun; Irawan, Dedi; Azhar, Aidil (JURNAL MANAJEMEN PENDIDIKAN ISLAM AL-IDARAH, 2017)
This study aims to describe the role of principal as a motivator in improving the professionalism of teachers' performance in SDN 2 kalirejo pesawaran. Data collection is done by conducting observation, interview, and documentation. Data analysis used was qualitative descriptive analysis. The technique of checking the validity of the data used in this study is to use triangulation of sources, that is by comparing the data of observations with the data of interviews and comparing the results of interviews with the contents of a related document.The results of the study show: The role of Headmaster as a Motivator in Improving Teacher Professionalism at SDN 2 Kalirejo Includes: the principal is able to create harmonious working relationships among teachers, able to create harmonious relationships among employees able to apply reward principles, Punishment), able to apply / develop internal and external motivation for school residents. The Role of School Principal As a Motivator in Improving Teacher Professionalism at SDN 2 Kalirejo has been running well, although in the implementation there are still many obstacles and obstacles in each component of madrasa management field.